2023
DOI: 10.1021/acs.iecr.3c00585
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Drying of Soybeans in Conical Spouted Beds: Modeling Approach

Abstract: Intermittent drying is a promising methodology to conventional drying which offers benefits related to energy and better-quality products. However, modeling of this technique remains a challenge. Thus, this study aims to propose a fully predictive model for intermittent drying in conical spouted bed dryers. A single-phase model is used to account for the heat and mass transfer on the soybean surface and their inside, and the predictions are compared with the experimental results. The proposed model provides ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…de Brito et al have reported that intermittent drying represents a promising alternative to conventional drying methods, offering advantages related to energy efficiency and improved product quality. Consequently, this study aims to present a comprehensive predictive model for intermittent drying in conical spouted bed dryers.…”
Section: Introductionmentioning
confidence: 99%
“…de Brito et al have reported that intermittent drying represents a promising alternative to conventional drying methods, offering advantages related to energy efficiency and improved product quality. Consequently, this study aims to present a comprehensive predictive model for intermittent drying in conical spouted bed dryers.…”
Section: Introductionmentioning
confidence: 99%
“…Continuum approaches typically represent the drying medium and granular solids as a dilute (i.e., bubble) phase, an interstitial gas phase, and a solids phase. Heat and mass transfer between phases is modeled using correlations to determine hydrodynamic parameters in a spouted bed. , The modeling of intermittent drying is also reported . Other conventional modeling approaches found in the literature include the population balance model (PBM), , neural network, and pore network model .…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to highlight that spouted bed drying is a field that still deserves being further explored. Recent studies have developed new technologies for spouted bed drying, such as the introduction of internal bed devices as the fountain confiner (Sukunza et al, 2023;Sukunza et al, 2024), mechanical stirrer (Pinto et al, 2023), and applied different drying techniques such as the intermittent drying (de Brito et al, 2023).…”
mentioning
confidence: 99%